Ergonomic Investigations of Asymmetrical Manual Lifting Tasks on Indian Male Workers - Singh, Ravindra Pratap (My University, 2015)
In India, manual material handling tasks are very common in manufacturing industry and construction sites. Manual lifting activities involve moving construction materials at sites loading and unloading of jobs on machines or lifting and moving materials from one location to another with varying frequency and sometimes with asymmetrical postures. The incidence, severity and potential disability of musculoskeletal injury are in many cases directly related to the kind of manual material handling jobs entrusted to the workmen in the workplace. There is thus a need for a scientific study to investigate into the effect of performance of such jobs on human health. The present research work was undertaken to carry out experimentation on healthy workmen using different task parameters during manual material handling and determine the safe limits and a parametric combination of lifting tasks. The work was completed in two phases. In the first phase, an experimental study was conducted to evaluate the effect of lifting task parameters and their interactions in different ambient temperature conditions on the heart rate and oxygen uptake of workers involved in manual lifting tasks. Workers were involved in lifting a loaded container from different levels asymmetrically and placing these at target locations at different levels as per the designed experimental conditions. Experiments were conducted in two different ambient temperature conditions. The climate of north western region of India has extreme variation of temperature over the year. The temperature in summer varies between 30 and 45° C while in winters, the minimum temperature goes even below 50 C on some days. Further, high humidity levels cause very harsh work conditions for workers involved in manual material handling tasks. Therefore effect of environmental conditions (heat and cold) should be considered as an integral component of the lifting process. The most significant lifting parameters and their ranges for this work were selected on the basis of pilot experimentation. An experiment study was carried out by using Taguchi’s L27 orthogonal array. Load weight, lift frequency, coupling (grip), asymmetric angle (posture), vertical distance (lifting height), horizontal distance from the object and travel distance (carrying distance) were the input process parameters (control factors) that constituted the orthogonal array. Temperature, a noise factor has been assigned to the outer array to study its effect. The set of twenty seven experiments were repeated three times for each combination of seven lifting parameters during the first phase. The main aim was to study the effect of variation in ambient temperature condition on the exertion caused to the worker in a lifting task. The interactions effect of some of these lifting parameters was studied by using a parameterization approach. Analysis of Variance (ANOVA) was used for the significance and percentage contribution of the significant factors. The design matrix was prepared for the identification of safe combinations of significant parameters as compared with the safe limits in different ambient conditions. The mean oxygen uptake and heart rate were calculated for all combinations of contributing factors using the Taguchi’s additive model the correction coefficients were then obtained statistically for these factors. The multiplicative equations using the task parameters were developed to calculate Predicted Heart Rate (PHR) and Predicted Oxygen Uptake (POU) for quick assessment of a manual lifting task. Both the responses (oxygen uptake and heart rate) were optimized simultaneously with Multi-Response Signal to Noise (MRSN) ratio obtained by normalization of S/N ratio of responses. MRSN was analyzed using ANOVA to identify the optimal condition. A regression equation was also developed to predict the response values in similar work conditions. In the second phase of the study, experiments were carried out to analyze the affect of lifting task parameters (lifting weight, frequency, coupling, asymmetric angle, vertical, horizontal and travel distances) on the ground reaction forces of workers using Taguchi’s Fractional Factorial Experiments design (L27) during lifting tasks. Workers lifted and placed a loaded container as per experimental design. Measuring ground reaction forces (force platform, Kistler 9286AA, 200 Hz) gives a good measure of musculoskeletal stresses of the workers performing such task. Loading rate was calculated from the graphical output of vertical reaction force obtained from the force platform. The results were analyzed using analysis of variance for identification of significant factors. The combinations of all significant factors were used to calculate the optimal loading rate using the Taguchi’s additive model. The design matrix has been made to identify the safe combinations of significant parameters for achieving safe limits in lifting tasks. Loading rate was predicted using an artificial neural network model. The lifting task parameters; lifting frequency, load, vertical distance, horizontal and travel distances were used as inputs to the model. Statistical tests were applied to find out the relation between the experimental and predicted values. The neural network model can be used to predict the exertion in performing the manual lifting task. Four responses; namely oxygen uptake, heart rate, perceived exertion and the ground reaction forces of workers were optimized collectively using the Analytical Hierarchy Process (AHP). Three samples were prepared according to frequency levels. The safe limits of all the responses were calculated using safe combinations of significant parameters in first and second phase of the study. The best suitable settings of parameters for safe lifting were evaluated using this method. It can be concluded from the present research work that ambient temperature affected the oxygen uptake and heart rate significantly during manual material handling tasks. Load weight, lifting frequency and vertical distance were found to be the most significant factors affecting all responses. Some interactions (load and lifting frequency etc) also showed their effect on cardiopulmonary responses. Workers should have some relaxation to overcome the exertion in winters and the limits of significant parameters can be increased without causing higher exertion to the workers under controlled temperature conditions. It was also observed that vertical reaction forces are more when worker lifts the weight from floor to shoulder height with high frequency and instantaneous loading rate increases with increase in weight, vertical distance and frequency. The safe limits of various responses can be used to design manual lifting tasks without any musculoskeletal injury/low back strain.
Ph.D.
Keywords: Ergonomics; Lifting Task